(untitled) (Ozone Therapy Global Journal, 2015)
Libro de resúmenes IV Congress of International Medical Ozone Federation (IMEOF) I Congress of the The Cuban Ozone Therapy Society (SCO), V Congress of Mexican Ozone Therapy Association (AMOZON) Havana, Cuba, Friday 27th – Sunday 29th November 2015. «Regularization, unity and science for worldwide ozone therapy” «Regularización, unidad y ciencia en pro de la ozono terapia mundial»